Primary Extranodal Non-Hodgkin Lymphoma of the Head and Neck in Patients with Acquired Immunodeficiency Syndrome: A Clinicopathologic Study of 24 Patients in a Single Hospital of Infectious Diseases in Argentina - Marcelo Corti (International Archives of Otorhinolaryngology, 2014)
Abstract